2011
DOI: 10.3892/ijo.2011.1140
|View full text |Cite
|
Sign up to set email alerts
|

Androgen deprivation therapy affects BCL-2 expression in human prostate cancer

Abstract: Abstract. BCL-2 is an integral protein of the external mitochondrial membrane that inhibits cell apoptotic death. We investigated the effect of androgen deprivation therapy (ADT) on BCL-2 expression in prostate cancer tissues. We studied BCL-2 expression in vivo in prostate cancer tissues obtained from patients who underwent radical prostatectomy after neoadjuvant ADT, by Northern and Western blot analysis, and immunohistochemistry. Moreover, gene transcriptional activity was also measured by nuclear run-on ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Tumors containing the TMPRSS2-ERG fusion were found to have higher expression of proliferation-related genes at baseline, which was significantly reduced by ADT, suggesting androgen dependence despite the fusion event 25 . In contrast Bcl-2 protein expression in PC was found to increase after exposure to ADT, though this occurred despite a lack of increase in mRNA levels for the gene 26 . A study comparing tissue from patients exposed to neoadjuvant chemohormonal therapy to untreated prostatectomy specimens found that androgen receptor expression was not different, but steroidogenic enzyme expression (CYP17, SRD5A1) was increased 27 .…”
Section: Molecular Outcomes Of Neoadjuvant Systemic Therapymentioning
confidence: 69%
“…Tumors containing the TMPRSS2-ERG fusion were found to have higher expression of proliferation-related genes at baseline, which was significantly reduced by ADT, suggesting androgen dependence despite the fusion event 25 . In contrast Bcl-2 protein expression in PC was found to increase after exposure to ADT, though this occurred despite a lack of increase in mRNA levels for the gene 26 . A study comparing tissue from patients exposed to neoadjuvant chemohormonal therapy to untreated prostatectomy specimens found that androgen receptor expression was not different, but steroidogenic enzyme expression (CYP17, SRD5A1) was increased 27 .…”
Section: Molecular Outcomes Of Neoadjuvant Systemic Therapymentioning
confidence: 69%
“…Bcl-2 has also been implicated in the development of androgen independent prostate cancer because of its increased expression in the advanced stages of disease ( 97 , 98 ). It is suggested that androgen-mediated mechanisms may act through Bcl-2-mediated apoptotic pathways ( 99 ).The overexpression of Bcl-2 in prostate cancer safeguards the tumor cells from apoptosis ( 100 , 101 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, Ohigashi's data indicated that herbimycin A-sensitive tyrosine kinase(s) can regulate apoptosis and inhibit Bcl-2 expression in SC2G mouse androgen-dependent cells 32 . Fuzio et al 33 analyzed Bcl-2 expression in vivo in prostate cancer tissues obtained from patients who underwent radical prostatectomy after neoadjuvant androgen deprivation therapy (ADT). They found that short-term administration of ADT interferes with Bcl-2 expression, thereby suggesting that androgen-mediated mechanisms may act through Bcl-2-mediated apoptotic pathways.…”
Section: Discussionmentioning
confidence: 99%